CD19.CAR T cells versus obinutuzumab - who will win the race for use in deep B cell depletion therapy in systemic autoimmunity? - Kvacskay, Peter; Merkt, Wolfgang (Rheumatology, 2024)
Over recent months, a number of noteworthy case reports and small case series have reported safety and unprecedented efficacy for CD19-targeting Chimeric Antigen Receptor (CAR) T cell therapy in various severe and refractory autoimmune diseases. A new milestone in innovative, cell-based treatment in systemic autoimmunity is on the horizon. Treatment with CD19-targeting CAR T cells is now an established therapy in haematology, and it is increasingly being suggested for the treatment of various non-malignant diseases [1]. The first use of anti-CD19.CAR T cells in rheumatology was in a patient affected by severe SLE, and significant clinical and serological improvement was observed after the treatment [2].